The MRI-Visible Nanocomposite Facilitates the Delivery and Tracking of siRNA Loaded DC Vaccine in the Breast Cancer Model - Wu, Changqiang; Zhu, Wencheng; Jin, Rongrong; Ai, Hua; Xu, Ye (Frontiers in Oncology, 2021)
Dendritic cell (DC) vaccines have been recruited for the treatment of various cancers recently, but often function not well as expected, primarily for the highly complex in vivo immune circumstance. This proof-of-principle study is aimed to test the feasibility to intervene the in vivo behaviors of DC vaccines (DCVs) by introducing the siRNA-laden MRI nanoprobes into the cells, while providing visible information on their homing to lymph nodes. The N-alkyl-PEI2k-LAC/SPIO nanocomposites were prepared and characterized, showing favorable properties of siRNA transfection and MRI labeling efficiency in DCs. Cell viability assays revealed no observable impacts on survival and phenotype of DCs if the concentration of the complex was within 8 μg Fe/mL. Orthotopic mouse model of breast cancer were developed. The DCVs with nanocomposites labeled were adoptively transferred to start the treatment. MR imaging clearly visualized the homing of DCs into lymph nodes. At the end of the treatment, DCVs presented significantly better tumor suppression than that injected only by DCs or PBS (P < 0.05). Generally, the N-alkyl-PEI2k-LAC/SPIO nanocomposites offers a low-toxic, high-efficient MR imaging platform for siRNA transfection that can be used for in vivo tracking the vaccine cells as well as for regulating their functions.